Clinical benefit of AI-assisted lung ultrasound in a resource-limited intensive care unit - Nhat, PTH; Van Hao, N; Tho, PV; Kerdegari, H; Pisani, L; Thu, LNM; Phuong, LT; Duong, HTH; Thuy, DB; McBride, A; Xochicale, M; Schultz, MJ; et al. (BioMed Central, 2023)
Background: Interpreting point-of-care lung ultrasound (LUS) images from intensive care unit (ICU) patients can be challenging, especially in low- and middle- income countries (LMICs) where there is limited training available. Despite recent advances in the use of Artificial Intelligence (AI) to automate many ultrasound imaging analysis tasks, no AI-enabled LUS solutions have been proven to be clinically useful in ICUs, and specifically in LMICs. Therefore, we developed an AI solution that assists LUS practitioners and assessed its usefulness in a low resource ICU.